Melatonin is a redundant entraining signal in the rat circadian system - Houdek, Pavel; Nováková, Marta; Polidarová, Lenka; Sládek, Martin; Sumová, Alena (Hormones and behavior, 2016)
The role of melatonin in maintaining proper function of the circadian system has been proposed but very little evidence for such an effect has been provided. To ascertain the role, the aim of the study was to investigate impact of long-term melatonin absence on regulation of circadian system. The parameters of behavior and circadian clocks of rats which were devoid of the melatonin signal due to pinealectomy (PINX) for more than one year were compared with those of intact age-matched controls. PINX led to a decrease in spontaneous locomotor activity and a shortening of the free-running period of the activity rhythm driven by the central clock in the suprachiasmatic nuclei (SCN) in constant darkness. However, the SCN-driven rhythms in activity and feeding were not affected and remained well entrained in the light/dark cycle. In contrast, in these conditions PINX had a significant effect on amplitudes of the clock gene expression rhythms in the duodenum and also partially in the liver. These results demonstrate the significant impact of long-term melatonin absence on period of the central clock in the SCN and the amplitudes of the peripheral clocks in duodenum and liver and suggest that melatonin might be a redundant but effective endocrine signal for these clocks.
Keywords: signální transdukce; Signal Transduction; cirkadiánní rytmus; lokomoce; světlo; melatonin; Female; fotoperioda; krysa rodu Rattus; zvířata; potkani Wistar; Light; Darkness; Circadian Rhythm; ženské pohlaví; nucleus suprachiasmaticus; Rats, Wistar; epifýza mozková; Photoperiod; Rats; Locomotion; Animals; tma; Pineal Gland; Suprachiasmatic Nucleus; Melatonin